A secure message handler using microsoft cryptoapi - Eh Kan, Chessda Uttraphan (2003)
In this project, a message handler with security features is developed using Microsoft CryptoAPI. The source code is written in Visual Basic to take advantage of the extensive graphical features of the language. A Visual Basic module called clsCiyptoAPI was developed to make calls to the advapi32.dll where the functions for the CryptoAPI reside. This module comprises seven routines, which are; a ByteToArray routine, ConvertByteToHex routine, ConvertStringFromHex routine, ConvertStringtoHex routine, CreateHash routine, CiyptEncrypt routine, and CryptDecrypt routine. These routines were compiled together to form the Dynamic Link Library (DLL) file. This dll file serves as a reference for any Visual Basic application which needs to call the CtyptoAPI function. A simple application is also developed to illustrate how to use this module to develop the user applications. This application demonstrates how to hash, encrypt and decrypt the string and various types of files using several cryptography algorithms provided by the CiyptoAPI function. This project also shows how to use a cryptography technique in network systems.